Media, gender, and popular culture in India : tracking change and continuity - Dasgupta, Sanjukta (SAGE Publications, 2012)
In contemporary India, as one side of the coin celebrates traditional stereotypes, the other side subverts the same image, sometimes subtly, but often radically. The push and pulls of these factors are changing the cultural landscape of India decisively. This volume critiques media representations of popular culture and gender since the 1950s and tracks the changes that have taken place in Indian society. The authors give us incisive analyses of these transformations, represented through the candid lens of the camera in films, television, advertisements and magazines, all of which focus on gender and familial representations and patriarchal norms in Indian society. The strength of this book is that it rejects grand narratives in favour of the micro-politics of daily living. In the course of exploring the metamorphosis of India, the authors succeed in dissolving the boundaries between mass/low culture, elite/high culture and local/national/global affiliations.